Based E-LKPD development based problem based learning to improve students' creative thinking skills on acid-base material - Mariyana Mariyana; Wilda Syahri; Haryant Haryant (Pascasarjana Universitas Negeri Medan, 2023)
Students' creative thinking skills tend to be lowas found in SMAN 2 Muaro Jambi. Hal this is due to students' low learning interest in chemistry subjects. Therefore the teacher must be able to create creative learning such as developing a teaching media. This study aims to develop media-based E-LKPD Problem Based Learning to be able to improve students' creative thinking skills on acid-base material. The type of development research carried out is Research and Development using a combination approach, namely between qualitative and quantitative approaches. The qualitative approach is intended to analyze the development process which will be described in depth about the events that occurred during the research, while the quantitative approach is used to analyze the results and path analysis. Electronic student worksheets (E-LKPD) which were developed based on problem-based learning models using Page flip Professional 3D software using a 4-D model development design. In this development research, the last stage is to test the effectiveness of the product using type experimental research design equivalent time serises design so it uses one experimental class by measuring the value posttest each meeting 3 times using the E-LKPD media that has been developed in the format pfprj. Based on the results of the study that there are differences in learning out comes without using the media and when using the media, that is obtained a difference of 11.56. Every meeting there is an increase of 5 - 7 average score so that the media developed is effective for improving students' creative thinking skills.Keywords: Acid-base material; Creative thinking skills; E-LKPD; Problem based learning